The Effect of Ball Training Setter On Passing Accuracy of Female Volleyball Athletes of Untad Club (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine whether there is an effect of the training setter ball on the accuracy of the upper pass of the Untad women's volleyball club athletes. This type of research is an experimental study because the aim is to see the effects of a treatment. The sample in this study was some volleyball players in the Untad women's volleyball club athletes as many as 12 people. The results of this study indicate that the average value before being given the training setter ball training was 59.83, and after being given the training setter ball training, 72.17, so that there was an increase of 12.33. Based on the results of the test sample calculation where t count = 58.71 while t table at the 5% level with degrees of freedom (db) = n-1 = 11 is 1.796 so it can be concluded that H0 is rejected and Ha is accepted because the t count value is greater than t table, which is 58.71> 1.796. The results of the study indicate that there is an effect of the training setter ball on the accuracy of the upper pass of the Untad women's volleyball club athletes.